Wireless sensor networks : a cognitive perspective - Ibnkahla, Mohamed (Adaptation in wireless communications., 2013)
"Preface Every day, Wireless Sensor Networks are gaining in popularity and applications. They are now widely used and deployed in key areas such as smart homes and buildings, intelligent transportation, health care, public health, military, food safety, water quality, smart power grid, industrial processes, precision agriculture, security, environment, etc. Various types of data with different rates and requirements are to be transmitted through these networks. Users are always in need for better coverage, connectivity, security and energy efficiency while looking for miniaturized, low-cost, and autonomous devices. Due to these requirements, classical techniques used in this field will soon reach their limitations and will no longer fulfill users' requirements. Cognitive communications is a new concept that emerged few years ago and has proven its importance, especially in the field of Cognitive Radio. This concept has been generalized to cover all aspects of the wireless communications system design. Wireless sensor networks represent an excellent area where cognition and intelligence can be easily developed and exploited not only to benefit the network efficiency and user requirements, but also to create new needs and new applications. This is because wireless sensor networks are, by nature, distributed systems where information can be made available about "everything" in the deployment area. Information may include user needs, user requirements, environment conditions, network conditions, node-level information (such as battery level, transmission range, processing capabilities, position information), etc. Security is also an important issue wherethe cognitive concept can play a key role"--